Sarawak Peat Characteristics and Heat Treatment - N.M, Sa'don; A. R, Abdul Karim; W., Jaol; W.H, Wan Lili (Universiti Malaysia Sarawak, 2015)
Peat layer is extensively scattered over the land of Malaysia. In Sarawak alone, peatland represents 13 percent (about 1.66 million hectares) of Sarawak’s total land area. They are present, mostly in low-lying areas; with in some areas, peat exceeding 10 m in depth. During past few decades, the demands on development of land were expanded into the swamp and deep peat areas which cannot be avoided. Thus proper management and construction practices should be emphasized, in order to overcome consequential occurrence of ground subsidence problems. The objectives of this study are to determine the characteristics of Sarawak peat, their empirical correlations as well as the effect of heat treatment on peat. The samples were taken from Matang, Batu Kawa, and Kota Samarahan sites, in Sarawak. The characteristic tests consist of degree of humidification, loss on ignition, Atterberg limit, particle density, moisture content and pH value. The results recorded high moisture content and organic content of Sarawak peat. It is also being categorized under the hemic group with pH values ranging from 3 to 4. The heat treatments with temperatures ranging from 100°C to 400°C were used on the peat samples. Samples collected were undergoing heat treatment and changes to its physical characteristic were compared with the original Sarawak peat. It was found that the heat treatments do influence the physical properties of Sarawak peat and have shown significant reduction in the compression index determined through the empirical correlations.